Funding Postsecondary Education: A Full Tuition, Private Sector, Income Contingent Repayment Plan - McDonough, L. C.; Wright, R. E. (Canadian Journal of Higher Education, 1998)
This study proposes and analyses the feasibility of a private sector ICR in which investments in human capital are accorded the tax treatment typical of fixed capital investments. Under this proposal, income-contingent repayment loans issued and administered by the private sector would cover both the full tuition costs and living expenses of students attending Postsecondary Education (PSE) institutions. The public sector would guarantee the loans, as well as provide relevant information to the private sector lenders as required. Simulations suggest that the student and public sector shares in the proposed full fee and expense plan would be approximately the same as those under the current financing system with students' fees set at 50% of full tuition. The proposed plan promises to eliminate virtually all accessibility problems related to financial constraints. Moreover, the incentive structures attendant to the proposed ICR are consistent with the "coherent learning system" advocated by the Economic Council of Canada.